DISTURBANCE OF AN APOPTOSIS OF NEUTROPHILS AT A SEPSIS - X.-F. Shen (Sankt-Peterburg : NIIÈM imeni Pastera, 2018)
The sepsis represents life-endangering disturbances of functions of the internals caused by a dizregulyation of a macroorganism to the  infectious agent and is difficult interaction of pro-inflammatory and  antiinflammatory processes that not seldom defines the fate of  patients. The predetermining factor of a sepsis is the originator. The  immunosupression caused by the originator promotes generalization  of an infection, and the intensive bacteriemia caused by generalization leads to the accruing endotoxinemia that aggravates  immunosupression even more and leads finally to systemic inflammatory reaction — the main and most dangerous implication  of a sepsis. The syndrome of systemic inflammation with  uncontrollable emission of cytokines is the cornerstone of a sepsis.  The pathophysiology of a sepsis begins with impassioned inflammatory reaction which can last several days, and then passes  into more lingering immunosupressivny period where the outcome  depends on the immune system of the patient. Cellular apoptosis is  one of leaders in sepsis immunosupression development. In article  mechanisms of disturbance of an apoptosis of neutrophils are  described that, undoubtedly, affects weighting of a current of a  sepsis and as a result, a failure. Migration of neutrophils under  natural conditions includes four various phases which during a sepsis  are broken. The mechanisms worsening migration of  neutrophils, contributing to the development of a sepsis were  investigated in numerous scientific works. Authors of Peking  University offered schemes of a way of disturbance of an apoptosis  of neutrophils and migration of neutrophils at a sepsis. Despite the  extensive accumulated experience on studying of a pathogenesis of  septic states, there are no effective and specific remedies of fight  from a sepsis now. Perhaps, by prevention of disturbance of the  programmed death of a cell the cytokines developed anti-apoptotic,  caspase inhibitors will be.